Zakat Distribution in Minimizing Poverty Levels For Economic Development - Apriyani, Nur (Jurnal Iqtisaduna, 2024)
Poverty is one of the significant societal challenges in many countries. The government and social organizations have tried to reduce poverty through various programs and policies. One instrument recognized as having the potential to reduce poverty is zakat, a social obligation for Muslims to give a portion of their wealth to those who deserve it. The purpose of this study is to analyze the role of zakat in minimizing poverty. Zakat has great potential to help reduce poverty in Indonesia. Evaluate the effectiveness of zakat distribution by assessing the extent to which zakat has been effectively distributed to those entitled to receive it. Many zakat programs implemented have directly assisted individuals and families in need. As well as measuring the impact of zakat on the economic empowerment of zakat recipients. This can involve analyzing economic growth, creating jobs, and improving the economic welfare of zakat recipients. Zakat has also been used to develop program skills and training, positively impacting Zakat recipients' social and economic mobility. However, this study also identifies several challenges that must be overcome in implementing zakat to minimize poverty. Some of these include the need for more awareness about zakat and its distribution mechanisms, uneven distribution, and governance problems within zakat institutions.